Quantifying Barrovian metamorphism in the Danba Structural Culmination of eastern Tibet. (23rd September 2013) - Weller, O. M.; St‐Onge, M. R.; Waters, D. J.; Rayner, N.; Searle, M. P.; Chung, S.‐L.; Palin, R. M.; Lee, Y.‐H.; Xu, X.
Abstract: The Danba Structural Culmination is a tectonic window into the late Triassic to early Jurassic Songpan‐Garzê Fold Belt of eastern Tibet, which exposes an oblique section through a complete Barrovian‐type metamorphic sequence. Systematic analysis of a suite of metapelites from this locality has enabled a general study of Barrovian metamorphism, and provided new insights into the early thermotectonic history of the Tibetan plateau. The suite was used to create a detailed petrographic framework, from which four samples ranging from staurolite to sillimanite grade were selected for thermobarometry and geochronology. Pseudosection analysis was applied to calculate P – T path segments and determine peak conditions between staurolite grade at ∼5.2 kbar and 580 °C and sillimanite grade at ∼6.0 kbar and 670 °C. In situ U–Pb monazite geochronology reveals that staurolite‐grade conditions were reached at 191.5 ± 2.4 Ma, kyanite‐grade conditions were attained at 184.2 ± 1.5 Ma, and sillimanite‐grade conditions continued until 179.4 ± 1.6 Ma. Integration of the results has provided constraints on the evolution of metamorphism in the region, including a partial reconstruction of the regional metamorphic field gradient. Several key features of Barrovian metamorphism are documented, including nested P – T paths and a polychronic field gradient. In addition, several atypical features are noted, such as P – T path segments having similar slopes to the metamorphic field gradient, and T max and P max being reached simultaneously in some samples. These features are attributed to the effects of slow tectonic burial, which allows for thermal relaxation during compression. While nested, clockwise P – T – t loops provide a useful framework for Barrovian metamorphism, this study shows that the effects of slow burial can telescope this model in P – T space. Finally, the study demonstrates that eastern Tibet experienced a significant phase of crustal thickening during the Mesozoic, reinforcing the notion that the plateau may have a long history of uplift and growth.